Jagdmeuten, Fluchtverwandlungen, Trinkerhalluzinationen - Michael Lorper (Recherches Germaniques)
Crowds and Power, Elias Canetti’s main work published in 1960, is a blend of scientific and literary writing. It can be described as an “anthropological novel” (Schüttpelz) that combines knowledge from various fields such as ethnology, anthropology, psychiatry, biology, and physics. Canetti uses analogies to connect these disciplines and derive insights about allegedly primordial human characteristics, mostly drawing on scientific and mythical narrations. The article explores the concepts of crowd, pack, and transformation, highlighting two key consequences of Canetti’s approach. Firstly, he presents individual and social phenomena in a primitivist and naturalizing manner. Secondly, by invoking the dimension of fluidity and rejecting rigid categories, Canetti offers a critique of science and power that has been valuable until today.